2017
DOI: 10.1542/peds.2016-2454
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Juice and Change in BMI: A Meta-analysis

Abstract: Consumption of 100% fruit juice is associated with a small amount of weight gain in children ages 1 to 6 years that is not clinically significant, and is not associated with weight gain in children ages 7 to 18 years. More studies are needed in children ages 1 to 6 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
92
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 40 publications
4
92
0
1
Order By: Relevance
“…However, a recent experimental study in mice found no difference in adiposity by sucrose intake but did find differences by fat intake [34], suggesting that fat rather than sucrose drives over-consumption. Observationally, consumption of 100% fruit juice, which may contain as much sucrose as SSB, is unrelated to weight gain in children aged 7-18 years despite slight weight gain in younger children, although this observation has not been confirmed in an RCT [13]. Instead, the observed association of SSB with adiposity in Western populations could be due to modern patterns of sugary/fatty snacking characterized by high SSB consumption, rather to sugar itself [35].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, a recent experimental study in mice found no difference in adiposity by sucrose intake but did find differences by fat intake [34], suggesting that fat rather than sucrose drives over-consumption. Observationally, consumption of 100% fruit juice, which may contain as much sucrose as SSB, is unrelated to weight gain in children aged 7-18 years despite slight weight gain in younger children, although this observation has not been confirmed in an RCT [13]. Instead, the observed association of SSB with adiposity in Western populations could be due to modern patterns of sugary/fatty snacking characterized by high SSB consumption, rather to sugar itself [35].…”
Section: Discussionmentioning
confidence: 93%
“…However, some others showed small effects of SSB intake on weight or BMI, which may be more marked for increasing consumption of SSB on weight gain and among the overweight [5,11,12]. As a beverage containing naturally occurring sugars, 100% fruit juice was not associated with weight gain in children aged 7 to 18 years in a meta-analysis of observational studies [13], but no RCT to date has tested the effect of 100% fruit juice on adiposity in children.Given the inconclusive evidence concerning the effect of SSB on adiposity, assessing the association in settings with different confounding patterns can be helpful [14]. Unlike in Western developed settings, obesity is less clearly socially patterned in Hong Kong Chinese children [15,16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Committee on Nutrition also theorized that minimizing sweet liquids might lessen future consumption of sweet beverages, lowering the risk for obesity. A recent meta-analysis by Auerbach et al [41] found almost no support for a connection between 100% juice and obesity, however.…”
Section: The Introduction To Complementary Feeding: 6-12 Monthsmentioning
confidence: 96%
“…The World Health Organization guidelines state that consuming these products increases overall energy intake and may displace healthier foods from the diet, potentially leading to weight gain and increased risk of non-communicable disease [1]. Classifying 100% fruit juice as a drink that should be limited is not without controversy due to inconclusive evidence from multiple meta-analyses on the causal link between 100% fruit juice consumption and adverse health effects [2][3][4][5]. Nevertheless, 100% fruit juice is causally linked to tooth decay [6] and can contribute to excess calories to the diet [1], suggesting that 100% fruit juice is not an appropriate substitute for SSBs.…”
Section: Introductionmentioning
confidence: 99%